2020
DOI: 10.21608/mjae.2020.94970
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat Productivity to Irrigation Regimes and Nitrogen Fertilization Levels

Abstract: Wheat is the main cereal crop in Egypt. The gap between production and consumption is about 60%. Research efforts are needed to reduce this gap, therefore; the objective of this work was to study the effect of three water regimes as irrigation at 45%, 60% and 70% depletion of the available soil moisture, and three nitrogen fertilization levels on two wheat varieties (Giza 168 and Giza 171).The field experiments were carried out at Bahry El-Methaq region, Alexandria Governorate, Egypt during the two successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…Gafaar (2007) [10] reported the highest value of biological yield with increasing seed rate up to 400 grains m -2 in wheat crop. However, the current result was in contrast with results reported by Allam (2003) [2] where in wheat higher seed rates, higher number of plants and tillers failed to produce higher biomass yield. With regards to the irrigation interval, the result is in line with the findings of Aslam et al (2014) [3] who reported that wheat crop irrigated five times resulted in significantly maximum biological yield (13732 kg ha -1 ) while the minimum biological yield (8600 kg ha -1 ) was recorded in three irrigations.…”
Section: Aboveground Dry Biomasscontrasting
confidence: 99%
“…Gafaar (2007) [10] reported the highest value of biological yield with increasing seed rate up to 400 grains m -2 in wheat crop. However, the current result was in contrast with results reported by Allam (2003) [2] where in wheat higher seed rates, higher number of plants and tillers failed to produce higher biomass yield. With regards to the irrigation interval, the result is in line with the findings of Aslam et al (2014) [3] who reported that wheat crop irrigated five times resulted in significantly maximum biological yield (13732 kg ha -1 ) while the minimum biological yield (8600 kg ha -1 ) was recorded in three irrigations.…”
Section: Aboveground Dry Biomasscontrasting
confidence: 99%